Fontan procedure: Early outcomes of 87 consecutive patients in a tertiary care center. Issue 4 (19th February 2020) - Kilcoyne, Maxwell F.; Stevens, Randy M.; Mahan, Vicki; Gray, Patrick; Moulick, Achintya N.
Abstract: Al Absi and colleagues report their early results of the Fontan procedure in 87 consecutive patients between August 2008 and July 2017 in a tertiary care hospital. The use of the intra/extracardiac fenestration is a promising modification because it is unlikely to be occluded by surrounding tissue and may be associated with decreased pleural effusions, length of hospital stay, and incidence of postoperative arrhythmias.